Regulatory Eosinophils Suppress T Cells Partly through Galectin-10 - Lingblom, Christine; Andersson, Jennie; Andersson, Kerstin; Wennerås, Christine (The Journal of immunology (1950), 2017)
Eosinophils have the capacity to regulate the function of T cell subsets. Our aim was to test the hypothesis of the existence of a regulatory subset of eosinophils. Human eosinophils were incubated with T cells that were stimulated with allogeneic leukocytes or CD3/CD28 cross-linking. After 2 d of coculture, 11% of the eosinophils gained CD16 expression. A CD16hi subset of eosinophils, encompassing 1–5% of all eosinophils, was also identified in the blood of healthy subjects. FACS sorting showed that these CD16hi eosinophils were significantly stronger suppressors of T cell proliferation than were conventional CD16neg eosinophils. Human eosinophils contain stores of the immunoregulatory protein galectin-10. We found that Ab-mediated neutralization of galectin-10 partially abrogated the suppressive function of the eosinophils. Moreover, recombinant galectin-10 by itself was able to suppress T cell proliferation. Finally, we detected galectin-10–containing immune synapses between eosinophils and lymphocytes. To conclude, we describe a subset of suppressive eosinophils expressing CD16 that may escape detection because CD16-based negative selection is the standard procedure for the isolation of human eosinophils. Moreover, we show that galectin-10 functions as a T cell–suppressive molecule in eosinophils.